The impacts of spring basal and side dressing on maize yield - Ragán, Péter (Acta Agraria Debreceniensis, 2014)
The yield potential of maize is very high. According to Tollenaar (1983), maize yield potential is as high as 25 t ha-1 (absolute dry yield) which is the highest among all cereals. In order to fully utilise this high yield potential, proper nutrient replenishment is of chief importance among all agrotechnical factors. The aim of research was to examine the effect of nitrogen fertiliser applied as basal and side dressing on maize yield. The measurements were performed at the Látókép experiment site (47° 33’ N, 21° 26’ E, 111 m asl) of the Centre for Agricultural Sciences of the University of Debrecen on mid-heavy calcareous chernozem soil with deep humus layer in an established experiment in 2011, 2012 and 2013. The trial design was split-split-plot with two replications. Based on the experiment results, it can be established that the nutrient uptake of maize is greatly dependent on the amount of water store in the soil. From the aspect of the development of the maize plant and water supply, the most determinant factor was the distribution of precipitation over the growing season and not the amount precipitation. This is shown by the fact there was only 276 mm precipitation – which was favourably distributed – in 2012 to increase the availability of nutrients and the main average was the highest in this year (14.394 t ha-1). Spring basal dressing helped maize development in all three years even on chernozem soil which is well supplied with nutrients. Although the effect of side dressing did not result in any yield increase, it could still contribute to mitigating the stress effects caused by environmental factors. Altogether, nutrient supply adapted to the various development stages of maize can favourably affect the success of maize production.